Implementasi Virtual Tour Menggunakan Panoramic Sebagai Media Edukasi Dan Promosi Kampus - Rahma Dipa Salsabil; Samsudin Samsudin; Adnan Buyung Nasution (Journal of Information System Research (JOSH), 2022)
The State Islamic University of North Sumatra (UINSU) has four campuses spread across several places, one of which is the campus building IV of the State Islamic University of North Sumatra which is located on Jalan Lap.Golf, Kp. Central District, Pancur Batu District, Deli Serdang Regency. There are still many people who don't know about the IV campus building and have never come in person because the UINSU IV campus building has just finished construction and is ready to be occupied in 2021, then the size of the IV UINSU campus can make people who have never come will feel confused about the location the building on campus IV UINSU. This research uses image stitching method to create a panoramic image of the campus building. Virtual tour application can help many people and candidate students and can help reduce confusion about the location of buildings for people who are coming to campus IV for the first time